Instant messaging via internet: an effective and interactive dimension in language learning - Noor Azlinda, Zainal Abidin; Ezihaslinda, Ngah; Wan Jumani, Fauzi; Noor Raha, Mohd Radzuan (2009)
The Internet is now widely used by educators and students all around the world. Its technology helps to promote and attract students in language learning. From the early generation web tools such as e mail, forum, and bulletin boards, we are now utilizing the latter generation tools such as blogs and Instant Messaging such as Skype, Yahoo messenger and Google talk. All of the tools mentioned are used in collaborative learning. This paper will discuss the use of the instant messaging in language learning and its effectiveness. It is no doubt that this medium of communication is very popular among our students nowadays. However, can this tool help our students in learning language? In the study, students were taught Communication skills including interpersonal skills. Inputs were given on making greeting and closing conversation in formal and informal situations. Later, they were asked to sign up for Yahoo messenger or Skype and were asked to apply what they had learnt in class to the virtual communication. The study indicates that this Instant Messaging enables students to apply what they have learnt not only in face-to-face communication but also virtual communication. The study also shows that influence of culture also takes place when communicating virtually. It is obviously seen 1M can accommodate students' learning especially in communicating in other than their mother tongue language. Apart from that, ESL classroom can be more enjoyable because of the availability of the technology which students can use, in improving their communication skills.